Marx e la “correzione” di Saussure. Riflessioni ontologiche sulla moneta a partire dall’analogia con la “lingua” - Garofalo, Pietro (Rivista Italiana di Filosofia del Linguaggio, 2014)
In this essay I will attempt to reconsider the notion of "value" in the social ontology of money. In light of this I will try to draw some conclusions about the ontological status of money. The essay is divided into four main parts. In the first part I will try to outline the theoretical framework that is represented by Searlean social ontology based on a specific theory of language, that is, the “Theory of Speech Acts.” This model is critical to my approach. Indeed, F. de Saussure’s description of language will provide the starting point for my work. This allows me to place the notion of "value" at the center of my discourse. In the second part I will examine a famous excerpt from Course in General Linguistics in which the Swiss linguist introduces an analogy between money and language, hence between linguistic and economic value. I will consider the strengths and weaknesses of Saussure’s “analogy” and attempt a modification. To do this, in the third part, I will propose re-reading Saussure via a Marxian interpretation, relying on Bloomfield’s intuition: the affinity between the Marxian analysis of commodity and the method of structural linguistics. This analysis leads to two main theoretical outcomes. The first is that the notion of "value" and the analogy of Saussure allow me to shift the emphasis from the “object” to the “social practice,” which is neglected in Searlean analysis. The second is that Money is represented not only as a medium of exchange, but as the logical function operating in a social system of exchange that needs to “transubstantiate” itself time after time in a specific object, the coin.